A review of fertilizer management toward productivity of oil palm (Fertilizer placement method) / Aminurhadi Abdullah - Abdullah, Aminurhadi (Faculty of Plantation and Agrotechnology, 2017)
Today, Oil palm (Elaeis guineensis) and the palm oil industry become a great economic that give more benefit to Malaysia where the current production of 19 million metric tons of Crude Palm Oil and adds 8% to the country’s Gross Nation Income (GNI). In the oil palm cultivation, fertilizing is the single large cost value about 60% of the upkeep cost. In fact, fertilizer alone was constituted about 24% of the total production cost of oil palm in Malaysia. The objective review of fertilizer management to determine the most effective method of fertilizer application and to apply the fertilizer in the prescribe manner over the areas of the estate that are likely to result in most efficient uptake of nutrients and produce high yield. Fertilizer is an important input in oil palm plantations, and has to be managed efficiently for maximum return. In most areas in Malaysia, there are periods of high rainfall, steep terrain and high soil erosion when broadcast fertilizer application is not recommendation due to surface run-off losses. Without proper application and knowledge, the applied fertilizer can become wasted, useless and even cause pollution. However, fertilizer efficiency depends on the source and type of fertilizer, method of placement, rate, frequency and timing of application. Fertilizer application method must be determines to ensure that fertilizer use efficiency by the oil palm resulted in maximum yield and minimize the nutrient losses. From the review of previous result shows that application of fertilizer by general broadcast on circle, over the frond stack and outside the edge of the palm circle resulted in maximum yield respond. The application of fertilizer by subsoil placement was inferior to broadcast application. In fact, that burying fertilizer at 10cm depth reduce uptake considerably. Fertilizer should be placed where they can most readily be absorbed by feeding roots to result in growth and productive of crop. For the result and recommended that fertilizer be broadcasted to maximize their contact with feeding roots and give more effect to the production yield of oil palm.